Importancia de la educación moral en los niños de 3 a 5 años - Pacheco Olaya, Alexandra Jessica (2014)
The purpose of this research work is to design a proposal aimed to teachers and parents to promote moral values through fun and ludic activities in students of initial level of a Private School “Liceo Los Delfines”, to guide teachers on the importance of moral education for children from 3 to 5 years old . The design of this research is framed in the form of feasible project, based on a descriptive research , methods and tools to obtain qualitative and quantitative information, the population and the sample was used, it was deduced of 5 teachers 51,1 principal and parents…..